Internalization of Students’ Nationalism Sense through Outbound Learning Based on Local Wisdom - Yulis Jamiah; Fatmawati Fatmawati; Endang Purwaningsih (STKIP Singkawang, 2019)
Outbound learning is a system that aims to assist students' learning process, contains a series of activities designed in the open nature, thus influencing and supporting the students' internal learning processes. Learning processes that are appropriate and attractive to students will encourage them to optimize their potential. The potential of local wisdom which is owned by students can be developed, have strategic value to maintain national defense, can strengthen nationalism sense, and can build national faith identity. Students as social agents who function to conserve the values of local wisdom and as a social asset that is useful to bring up a nationalism sense. The value of local wisdom implemented in learning must be based on assets of local cultural values and open to global knowledge and technology. Internalization of the values of local wisdom derived from cultural products and community works as learning media, is useful to bring up nationalism awareness. The values of local community wisdom are still conserved from generation to generation by the community as a moral responsibility to keep the tradition from becoming extinct.